Gonadal malignancy in 13 consecutive collected patients with disorders of sex development (DSD) from Semarang (Indonesia). Issue 3 (25th December 2012) - Juniarto, Achmad Zulfa; Setyawati, Bestari A; Miranti, Ika P; Santosa, Ardy; Hersmus, Remko; Stoop, Hans; Cools, Martine; Oosterhuis, J Wolter; Drop, Stenvert L S; Faradz, Sultana M H; Looijenga, Leendert H J
Abstract : Aims: Caucasian patients with disorders of sex development (DSD) are at a high risk of developing germ cell cancer (GCC). GCC is prominent in young adults in Western countries, while the incidence is significantly lower in Asia. So far, the risk of GCC in Asian DSD patients is unknown. Methods and results: A detailed study of gonad histology, morphology and immunohistochemistry (OCT3/4, testis-specific protein Y-encoded, VASA, SCF/KITLG, SOX9, FOXL2) of 16 Indonesian DSD patients was undertaken. 13 cases could be analysed, including ovarian tissue (n=3), streak gonad (n=1), undifferentiated gonad (n=1) and testicular tissue (n=8), diagnosed as 46, XX (n=1), 46, XY (n=7) and sex chromosome DSD (n=5). The precursor lesion gonadoblastoma or carcinoma in situ, or GCC was diagnosed in four cases (30.8%; three 46, XY and one sex chromosome DSD ). A hormone producing ovarian Leydig cell tumour was identified in a 46, XX patient, supposed to be a late onset congenital adrenal hyperplasia. Conclusions: In spite of the significantly lower risk of GCC in the general Asian population, DSD is a dominant risk factor. The study demonstrates the power of immunohistochemical markers for (early) diagnosis. This knowledge will deepen understanding of the pathobiology of GCC and clinical handling of patients with DSD, globally.